Artificial hybridization test in peanut - dos Santos, Roseane Cavalcante; Farias, Francisco José Correia; Moreira, José de Alencar Nunes; Melo, Péricles de Alburquerque (Pesquisa Agropecuaria Brasileira, 1994)
Artificial hybridation is an usual method to obtain genetic variability in peanut (Arachis hypogaea L.) plant-breading programs. There are, however, some morphological aspects which make it difficult to obtain hydrids. A green house trial was set out in 1990 and 1991 at Centro Nacional de Pesquisa de Algodão, Campina Grande, PB, Brazil, to study the efficiency of two artificial hybridation techniques in peanuts, a conventional and a modified one. Genotypes of Valência and Virgínia groups were used as progenitors. They were grown in plastic containers in a sandloam texture soil. The result showed that no significant difference was obtained between techniques (chisquare test at 0.5 level). The modified technique can be recommended, because it requires 50% less manual work and reduces hand injury on flower structures.